2020
DOI: 10.3390/healthcare8030330
|View full text |Cite
|
Sign up to set email alerts
|

United States County-level COVID-19 Death Rates and Case Fatality Rates Vary by Region and Urban Status

Abstract: COVID-19 is a global pandemic with uncertain death rates. We examined county-level population morality rates (per 100,000) and case fatality rates by US region and rural-urban classification, while controlling for demographic, socioeconomic, and hospital variables. We found that population mortality rates and case fatality rates were significantly different across region, rural-urban classification, and their interaction. All significant comparisons had p < 0.001. Northeast counties had the highest populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
6
24
0
1
Order By: Relevance
“…Our study highlights a concerning disparity between urban and rural counties, consistent with several other studies, wherein urban counties experience higher incidence rates, yet rural counties experience higher case fatality rates [2, 22]. Moreover, our study is the first to identify Hispanic & African American populations, elderly populations, and large nursing homes as major contributing factors to this urban-rural disparity in Texas.…”
Section: Discussionsupporting
confidence: 89%
“…Our study highlights a concerning disparity between urban and rural counties, consistent with several other studies, wherein urban counties experience higher incidence rates, yet rural counties experience higher case fatality rates [2, 22]. Moreover, our study is the first to identify Hispanic & African American populations, elderly populations, and large nursing homes as major contributing factors to this urban-rural disparity in Texas.…”
Section: Discussionsupporting
confidence: 89%
“…These and other regional patterns [28,29] may not hold over a longer study time-period. Urban-rural disparities explored in earlier research found increased mortality rates [30] and higher prevalence rates of COVID-19 infection in urban counties [12]. Another study found higher standardized cases and fatalities in rural counties in just one US state [13], while others found severe negative impacts of the pandemic on rural unemployment and economic wellbeing [10].…”
Section: Socioeconomic and Spatial Disparities Of The Covid-19 Pandemicmentioning
confidence: 89%
“…ZCTAs are generalized representations of ZCs that have been assigned to census blocks and representative of the geographic locations of populated areas [ 25 ]. ZCTA boundaries were constructed utilizing shapefiles (.shp) and geodatabases (.gdb) from TIGER/Line Shapefiles [ 25 , 27 ]. In addition, the TIGER/Line Database was utilized to stratify county areas including/surrounding the ZCs as the following: urban cluster areas (2,500-<50,000 population), urbanized areas (50,000–99,999 population), and metropolitan areas (≥100,000 population).…”
Section: Methodsmentioning
confidence: 99%